عالمی سطح پر امن کے قیام میں اسلامی نظریات کی افادیت: The Usefulness of Islamic Ideologies in Establishing Peace on a Global Scale - Dr. Shazia; Taiba Ramzan (Al Manhal Research Journal, 2025)
The concept of peace in Islam is comprehensive, inclusive, and universal, setting it apart from all other ideologies. Far from being confined to spiritual or ritual aspects, Islam offers a complete code of life that promotes coexistence, justice, tolerance, and the dignity of humanity. It envisions a global order rooted in compassion and mutual respect. In today’s world, where religion is frequently linked with extremism and violence, the true essence of Islam is often distorted. This research seeks to highlight, with scholarly and historical evidence, that Islam is inherently a religion of peace. Through an in-depth exploration of the Qur'an, Prophetic traditions (Sunnah), and the life of the Prophet Muhammad ﷺ this paper aims to demonstrate how Islam emphasizes mercy, justice, forgiveness, and harmony at both individual and societal levels. Their insights have been carefully incorporated to support an authentic, balanced, and academically sound representation of Islam’s vision of global peace.